2012
DOI: 10.3389/fnhum.2012.00007
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Natural Numbers: Negative Number Representation in Parietal Cortex

Abstract: Unlike natural numbers, negative numbers do not have natural physical referents. How does the brain represent such abstract mathematical concepts? Two competing hypotheses regarding representational systems for negative numbers are a rule-based model, in which symbolic rules are applied to negative numbers to translate them into positive numbers when assessing magnitudes, and an expanded magnitude model, in which negative numbers have a distinct magnitude representation. Using an event-related functional magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 47 publications
3
22
0
1
Order By: Relevance
“…18 However in the Loss Treatment, subjects took more time to make their decisions (Fisher test, p-value = 0.006). It is in line with previous research that has suggested that polarity and numerical magnitudes of negative numbers are represented separately and thus associated with higher response times (Tzelgov et al, 2009;Blair et al, 2012 Being loss averse (under ambiguity) increases response times more in the Loss Treatment.…”
Section: Sdt-free Analysis At a Decision Levelsupporting
confidence: 92%
“…18 However in the Loss Treatment, subjects took more time to make their decisions (Fisher test, p-value = 0.006). It is in line with previous research that has suggested that polarity and numerical magnitudes of negative numbers are represented separately and thus associated with higher response times (Tzelgov et al, 2009;Blair et al, 2012 Being loss averse (under ambiguity) increases response times more in the Loss Treatment.…”
Section: Sdt-free Analysis At a Decision Levelsupporting
confidence: 92%
“…The abstract nature of negative number become main epistemological obstacles which occur in students (Almeida & Bruno, 2014;Altiparmak & Ozdogan, 2010;Blair , 2012;Larsen, 2012). This can occur because thus far student is introduced to number concept as a real thing.…”
Section: Undersmentioning
confidence: 99%
“…According to them, even though it seems easier in grade seventh and teachers in secondary schools, this material is quite difficult to be understood, particularly in operation of number which involves negative number. Unlike positive number, negative number has not perception referential which is clear, and therefore, students should try harder to learn about negative number (Blair et al, 2012). Many of these are very good models of the positive and negative numbers but difficulties arise when we use them to illustrate the operations of addition, subtraction, multiplication and division (Galbraith, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…Most previous research about RSA has been restricted to visual object recognition [51]. Recently, RSA has been recognized as a powerful tool and has been applied to a broad range of fields including auditory objects recognition [51], memory [52], language [53], emotion [54], number cognition [55], and olfaction [56]. For example, Xue et al [57] found that the degree of consistency in neural response patterns across repeated presentations of a stimulus was positively associated with later memory for that stimulus.…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%